Identifying HR Management and Supervision Activities at SMAN 1 Merangin to Face Society 5.0 and Industrial Revolution 4.0 - Taufik Ridho Iano; Nellitawati Nellitawati; Hanif Al Kadri (Jurnal Indonesia Sosial Teknologi, 2024)
The article explains the importance of managing and supervising human resources, especially teachers, in Society 5.0 and the era of Industrial Revolution 4.0, which is full of knowledge of technology and digital-based activities. The principal and the driving/developing teachers did this management and supervision effort. The author observed this, with the school being the main focus, SMAN 1 Merangin. This article uses a qualitative research method by prioritising the process of communication interaction and observation in research and a systematic literature review (SLR) method by collecting other sources regarding HR management and supervision in facing society 5.0 and the Industrial Revolution 4.0 from books, journals and other sources. The challenge faced by SMAN 1 Merangin based on the interview is how to get all teachers, or at least 50% of the teachers at SMAN 1 Merangin, to get a driving teacher certificate and other training certificates so that they can get out of the safe zone and become proficient in information technology. While facing this era, SMAN 1 Merangin teachers adept at technology and good at solving learning problems are appointed to drive teachers and supervise other teachers in collaboration with the school principal to improve performance and catch up with the times.